Automata, Languages, and Programming 40th International Colloquium, ICALP 2013, Riga, Latvia, July 8-12, 2013, Proceedings, Part I - Fomin, Fedor V.; Freivalds, Rusins; Kwiatkowska, Marta; Peleg, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This two-volume set of LNCS 7965 and LNCS 7966 constitutes the refereed proceedings of the 40th International Colloquium on Automata, Languages and Programming, ICALP 2013, held in Riga, Latvia, in July 2013. The total of 124 revised full papers presented were carefully reviewed and selected from 422 submissions. They are organized in three tracks focussing on algorithms, complexity and games; logic, semantics, automata and theory of programming; and foundations of networked computation.
Algorithms, complexity and games -- Logic, semantics, automata and theory of programming -- Foundations of networked computation.
Keywords: Algorithms; Computer science; 9; Information storage and retrieval systems; Application software; Computer science -- Mathematics; Discrete mathematics; Algorithms; Theory of Computation; Computer Communication Networks; Information Storage and Retrieval; Computer and Information Systems Applications; Discrete Mathematics in Computer Science